Land and Development in Indonesia : Searching for the People's Sovereignty - Robinson, Kathryn May, 1949-; McCarthy, John F. (John Fitzgerald), 1964- (Book collections on Project MUSE., 2016)
Indonesia was founded on the ideal of the 'Sovereignty of the People', which suggests the pre-eminence of people's rights to access, use and control land to support their livelihoods. Yet, many questions remain unresolved. How can the state ensure access_to land for agriculture and housing while also supporting land acquisition for investment in industry and infrastructure? What is to be done about indigenous rights? Do registration and titling provide solutions? Is the land reform agenda - legislated but never implemented - still relevant? How should the land questions affecting Indonesia's disappearing forests be resolved?The contributors to this volume assess progress on these issues through case studies from across the archipelago: from large-scale land acquisitions in Papua, to asset ownership in the villages of Sulawesi and Java, to tenure conflicts associated with the oil palm and mining booms in Kalimantan, Sulawesi and Sumatra. What are the prospects for the 'people's sovereignty' in regard to land?